Efficacy of a Satyananda Yoga intervention for reintegrating adults diagnosed with posttraumatic stress disorder (2015)
ABSTRACT: The prevalence of posttraumatic stress disorder (PTSD) in ex-combatants from illegal armed groups in Colombia has been estimated at 37.4%. This high prevalence indicates a need to explore alternative and adjunctive therapies in the treatment of PTSD. A randomized controlled trial was undertaken to evaluate the efficacy and safety of a protocol based on Satyananda Yoga® in PTSD-diagnosed reintegrating adults in Colombia. One hundred reintegrating adults (n = 50 for each of the yoga and control arms) from Bogota and Medellin participated in this study. Yoga participants engaged in a Satyananda Yoga intervention for 16 weeks while the control group continued the regular demobilization program. The Posttraumatic Stress Disorder Checklist - Civilian Version (PCL-C) was used to evaluate the effects of the applied therapy. Outcomes were assessed before entry and after the treatment. T-tests revealed a treatment effect of d = 1.15 for the yoga group and a between-groups effect size of d = .73. The difference in improvement in PCL-C scores between both groups was 18.91% (p < 0.05). The highest percentage of improvement was observed in the re-experiencing symptom cluster (23.71%; p < 0.05), with a treatment effect of d = 1.40 for the yoga group and a between-groups effect size of d = 1.15. The data suggest that Satyananda Yoga methodology is an effective therapy for reintegrating adults diagnosed with PTSD. Further research is needed in order to evaluate prolonged effects of this alternative therapy.